Exploring glutathione transferase and Cathepsin L-like proteinase for designing of epitopes-based vaccine against Fasciola hepatica by immunoinformatics and biophysics studies - Alhassan, Hassan H.; Ullah, Muhammad Ikram; Niazy, Abdurahman A.; Alzarea, Sami I.; Alsaidan, Omar Awad; Alzarea, Abdulaziz Ibrahim; Alsaidan, Aseel Awad; Alhassan, Abulaziz A.; Alruwaili, Muharib; Alruwaili, Yasir S. (Frontiers in Immunology, 2024)
Fasciolosis is a zoonotic infection and is considered a developing deserted tropical illness threatening ruminant productivity and causing financial losses. Herein, we applied immunoinformatics and biophysics studies to develop an epitopes vaccine against Fasciola hepatica using glutathione transferase and Cathepsin L-like proteinase as possible vaccine candidates. Using the selected proteins, B-cell and T-cell epitopes were predicted. After epitopes prediction, the epitopes were clarified over immunoinformatics screening and only five epitopes, EFGRWQQEKCTIDLD,RRNIWEKNVKHIQEH,FKAKYLTEMSRASDI, TDMTFEEFKAKYLTE and YTAVEGQCR were selected for vaccine construction, selected epitopes were linked with the help of GPGPG linker and attached with adjuvant through another linker EAAAK linker, Cholera toxin B subunit was used as an adjuvant, The expasy protparam tool the server predicted 234 amino acids, 25.86257-kilo dalton molecular weight, 8.54 Theoretical pI, 36.86 instability index and -0.424 Grand average of hydropathicity. Molecular docking analysis predicted the vaccine could activate the immune system against F. hepatica. We calculated negative binding energy values. A biophysics study, likely molecular docking molecular dynamic simulation, further validated the docking results. In molecular dynamic simulation analysis, the top hit docked compounds with the lowest binding energy values were subjected to MD simulation; the simulation analysis showed that the vaccine and immune cell receptors are stable and can activate the immune system. MMGBSA -146.27 Net Energy (kcal/mol) was calculated for the vaccine-TLR-2 complex while vaccine-TLR-4 -148.11, Net Energy (kcal/mol) was estimated. Further, the C-ImmSim bioinformatics tool predicted that the vaccine construct can activate the immune system against F. hepatica, eradicate the infection caused by F. hepatica, and reduce financial losses that need to be spent while protecting against infections of F. hepatica. The computational immune simulation unveils that the vaccine model can activate the immune system against F. hepatica; hence, the experimental scientist can validate the finding accomplished through computational approaches.